Measuring food fortification coverage in household surveys: Formative research findings from Bangladesh and Ethiopia - Scott, Samuel P.; Myers, Emily; Jungjohann, Svenja; Manohar, Swetha; Neupane, Sumanta; Banerjee, Archis; Berhane, Hanna; Workneh, Firehiwot; Ferdaweke, Fiker; Zaman, Zubayer Ibn; Salsabil, Nishat; Billah, Sk Masum; et al. (F1000 Research Ltd, 2025)
Background Large-scale food fortification (LSFF) is a cost-effective approach used in most countries to address widespread micronutrient deficiencies. Understanding who consumes fortified foods is challenging as these foods are often undetectable by design. The objective of this work was to refine survey items used to measure LSFF coverage for their potential use in routine multitopic household surveys.